Trabalho infantil no distrito de Pinheiros na cidade de São Paulo: reflexões sobre as possibilidades da intersetorialidade na perspectiva preventiva do trabalho infantil - Carmo, Itamar Moreira do (2023)
This research aims to study child labor in the district of Pinheiros in the city of São Paulo, reflecting on the possibilities of intersectorality in the preventive perspective of child labor.The objective of this study is to analyze child labor and prevention and social protection devices based on the experiences of care provided by the Specialized Social Approach Services (SEAS), in the district of Pinheiros/SP, and the work with families carried out by the Services of Family Social Assistance and Basic Social Protection at Home (SASF), in the community of origin of children and adolescents, developed by the Municipal Secretariat for Social Assistance and Development (SMADS).The research methodology was developed from a critical perspective, using qualitative approaches, combining bibliographical, documentary, and empirical research with pre-defined subjects.The research results point to the importance of intersectoral work in combating child labor